The influence of waste printed circuit boards characteristics and nonmetal surface energy regulation on flotation. (October 2018) - Han, Jun; Duan, Chenlong; Li, Guofeng; Huang, Long; Chai, Xuesen; Wang, Dan
Graphical abstract: Highlights: The influence of waste PCBs characteristics on flotation was examined. The nonmetal SE was calculated and the particles interaction was studied by EDLVO. The agglomeration of nonmetal was solved by regulation surface energy using tannin. The mechanism of pharmacy dispersion and adsorption were expound. The flotation efficiency of PCBs was enhanced by improving nonmetal dispersion. Abstract: This paper studied the influence of waste printed circuit boards (PCBs) characteristics and nonmetal surface energy (SE) regulation on flotation. First, SEM-EDS was applied to study the appearance and surface element distribution of the glass fiber and copper. The results showed that the glass fiber was present in a bundle and the surface carbon content was 49.42%, which facilitated glass fiber floating. The copper appearance contained many nodules, with a carbon content of 32.54%, which hindered copper sorting. XPS analysis further discovered that copper was mainly present in the forms of CuO, Cu(Met), and Al2 Cu. A FT-IR analysis revealed that the organic matter in the PCBs was essentially the same as the epoxy resin. It was easy to achieve floating and some polar functional groups promoted the adsorption of the flotation reagents. Based on this, by calculating the nonmetal SE, it was found that the proportion of the non-polar component of the nonmetal SE was 94.60%. The EDLVO theory was applied to research interactions between nonmetal particles. Hydrophobic attraction was found to be the main factor causing nonmetal particles to agglomerate. Further, the tannin was used to improve the dispersion of nonmetal by adjusting the nonmetal SE. Furthermore, the hydroxyl and carbonyl groups in the tannin may form hydrogen bonds with the bromine, epoxy and hydroxyl groups in the nonmetal. Finally, flotation test results indicated that tannin added significantly enhanced PCBs flotation efficiency. When the amount of tannin added increased from 0 to 60 mg/L, the recovery of copper increased from 61.92% to 90.53%. Thus, this study provides an alternative approach to improve the flotation efficiency of waste PCBs.